Integrating Artificial Intelligence in Islamic Education Management: Challenges and Opportunities in the Digital Era - Said Maskur; Hasyamuddin Bin Othman (PT. Hassan Group Publisher, 2025)
The integration of Artificial Intelligence (AI) in Islamic education management has become a significant development in the digital era, offering opportunities to enhance teaching, learning, and institutional governance while upholding Islamic values and ethical principles. This study aims to analyze the challenges and opportunities associated with AI implementation in Islamic higher education institutions, focusing on how innovation can align with maqasid al-shariah and pedagogical traditions. Using a qualitative descriptive-analytical design, data were collected through in-depth interviews with educational leaders, lecturers, and IT experts from five Islamic universities in Indonesia and Malaysia, supported by document analysis of institutional policies and AI implementation frameworks. The findings reveal that AI facilitates personalized learning, predictive analytics, and administrative efficiency, strengthening academic performance and institutional competitiveness. However, significant challenges remain, including algorithmic bias, data privacy concerns, and the potential erosion of educators’ roles in character formation